2015
DOI: 10.1542/peds.2014-0760
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Exclusive E-Cigarette Use and Dual E-Cigarette Use and Tobacco Use in Adolescents

Abstract: To describe electronic cigarette (e-cigarette) use and cigarette use among adolescents and determine whether established risk factors for smoking discriminate user categories.METHODS: School-based survey of 1941 high school students (mean age 14.6 years) in Hawaii; data collected in 2013. The survey assessed e-cigarette use and cigarette use, alcohol and marijuana use, and psychosocial risk and protective variables (eg, parental support, academic involvement, smoking expectancies, peer smoking, sensation seeki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

51
351
2
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 374 publications
(412 citation statements)
references
References 42 publications
51
351
2
8
Order By: Relevance
“…6,9,10,12,15 Among youth, self-reported e-cigarette use was also associated with higher odds of ever or current conventional cigarette smoking. 15 Compared with nonusers, youth who used e-cigarettes perceived them as healthier than cigarettes 10 ; however, youth using e-cigarettes were less likely to achieve abstinence from conventional cigarettes. 15 Youth exposure to ENDS secondhand and thirdhand aerosol has also potentially increased with the increase in adult ENDS use.…”
Section: Epidemiology Of Youth Ends Usementioning
confidence: 99%
See 3 more Smart Citations
“…6,9,10,12,15 Among youth, self-reported e-cigarette use was also associated with higher odds of ever or current conventional cigarette smoking. 15 Compared with nonusers, youth who used e-cigarettes perceived them as healthier than cigarettes 10 ; however, youth using e-cigarettes were less likely to achieve abstinence from conventional cigarettes. 15 Youth exposure to ENDS secondhand and thirdhand aerosol has also potentially increased with the increase in adult ENDS use.…”
Section: Epidemiology Of Youth Ends Usementioning
confidence: 99%
“…[6][7][8][9] Other surveys of high school students have found higher current use at 17% to 18%, with ever use as high as 29%. 10,11 The 2014 NYTS and Monitoring the Future survey both documented for the first time that more teenagers used e-cigarettes in the past 30 days than any other tobacco products, including conventional cigarettes. 8,11 ENDS use has been documented as highest among male subjects, non-Hispanic white youth, and Hispanic youth.…”
Section: Epidemiology Of Youth Ends Usementioning
confidence: 99%
See 2 more Smart Citations
“…Based on current research of Big Five Model of Personality Structure, personality dimensions correlate positively with risk behavior [12][13][14], but they correlate negatively with unexcused absence from school as well as with cigarette and alcohol use [15]. Previous study on correlation between personality dimensions and risky health behavior has shown that agreeableness correlates negatively with alcohol and cigarette use among both sexes, neuroticism and introversion correlate positively with female adolescents, while extroversion correlates positively with male adolescents [16].…”
Section: Introductionmentioning
confidence: 99%